2017
DOI: 10.1109/twc.2017.2664829
|View full text |Cite
|
Sign up to set email alerts
|

A Geometry-Based Underwater Acoustic Channel Model Allowing for Sloped Ocean Bottom Conditions

Abstract: Abstract-This paper proposes a new geometry-based channel model for shallow-water ocean environments in which the ocean bottom can slope gently down/up. The need for developing such an underwater acoustic (UWA) channel model is driven by the fact that the standard assumption of a flat ocean bottom does not hold in many realistic scenarios. Starting from a geometrical model, we develop a stochastic channel model for wideband single-input single-output vehicle-to-vehicle UWA channels using the ray theory assumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…• It is generally considered safe to assume the sea surface as a flat plane in underwater acoustic wave propagation, but this is not the case for the seafloor. In the work done by Naderi et al [83], the up/down slopes in seabed have been taken into account. This important consideration is particularly essential in the case of shallow waters in the presence of coral reefs and plants, and cannot be neglected.…”
Section: E Underwater Channel Modelingmentioning
confidence: 99%
“…• It is generally considered safe to assume the sea surface as a flat plane in underwater acoustic wave propagation, but this is not the case for the seafloor. In the work done by Naderi et al [83], the up/down slopes in seabed have been taken into account. This important consideration is particularly essential in the case of shallow waters in the presence of coral reefs and plants, and cannot be neglected.…”
Section: E Underwater Channel Modelingmentioning
confidence: 99%
“…Authors in [32] consider a random distribution of Scatterers and rough condition of the surface and bottom ocean. A new geometry-based channel model raises up [33] for shallow UAC in which slopped ocean bottom is considered. It's shown that even a small slopped bottom has a significant impact on the UACs statistical properties.…”
Section: B Dynamic Underwater Acoustic Propagation 1) Time-varying Distortionmentioning
confidence: 99%
“…Near the ocean surface, however, both the pressure and temperature are generally invariant, resulting in a constant sound speed [4]. Therefore, the shallow-water ocean environment is regarded as an isovelocity environment [24]. Fig.…”
Section: A a Geometry-based Channel Modelmentioning
confidence: 99%
“…, and the time delay τ nm L (t) denotes the travel time of the LoS macro-eigenray between the nth hydrophone and the mth transducer. Similar to [24], the DA and UA components of the time-variant channel impulse response are, respectively,…”
Section: αT αRmentioning
confidence: 99%